Perancangan Sistem Alat Pengering Rumput Laut Otomatis dengan Pengintegrasian Panel Surya - Sah Putra, Al Fiillian; Purnama, Yowarigo Putra; Pratama, Shandy; Naufal, Diaz; Sahrupi, Sahrupi (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Global demand for processed seaweed products, including gelatin, continues to increase. In 2018, the total global demand for carrageenan was estimated at USD 275,188,000, an increase of 4.9% from the previous year, and the total global demand for carrageenan was recorded at USD 1,131,820,000, an increase of 8.4% from the previous year. This research aims to create a tool that can accelerate seaweed drying time. The result of this research is the design of a seaweed stingo uno prototype. Seaweed Stingo Uno is a system designed with the aim of speeding up seaweed production time. The production time that will be accelerated is the drying time. This system is integrated with the ability to produce electrical energy naturally using solar panels. This integration functions so that the tool can work without having to use conventional electrical energy. The hope is that the tools developed can be applied both in small-scale and large-scale industries in seaweed production. Future research can carry out tool testing in the laboratory and field to obtain valid and reliable tools. Keywords: Drying Equipment, Seaweed, System Modeling